Linear and nonlinear optical characterisation of silicon nanowire structures - McNicholas, Sharon Mary (Trinity College (Dublin, Ireland). School of Physics, 2008)
The morphological and optical properties of various silicon nanowire structures were investigated. Photoluminescence was produced by all of the nanostructures and was attributed to a variety of different mechanisms. Optical limiting capabilities were also demonstrated by the sihcon nanostructures in isopropanol dispersions. The observed optical limiting has a strong contribution from non-linear scattering. It is likely that the non-linear scattering arises due to plasmas, which are formed by laser induced breakdown of the nanostructure's silicon oxide outer shells.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin